Peningkatan Prestasi Belajar Ilmu Pengetahuan Alam tentang Energi dan Perubahannya Melalui Pendekatan Mastery Learning pada Siswa Kelas VI SD Negeri 3 Kalikotes Kabupaten Klaten - Endang Sumarsih (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2015)
This research is the context of increasing student achievement special subjects of Natural Sciences of Energy and its amendment through Mastery Learning approach. Subject and source of research data as many as 25 students. Data collection method used observation, documentation, and testing. Analysis of data using critical and comparative analysis. Results of research and discussion are (1) the data obtained from precycle until the second cycle, obtained progress of student achievement in the learning of Natural Sciences at the material Energy and its amendment is average of 72.1 and the first cycle by an average of 76.5 and the second cycle by an average of 84.2. From this, it seems clear that an increase in the average value of precycle to the first cycle of 4.4 figure (6.1%), from the first cycle to the second cycle there is an increase of 7.7 figure (10%), from precycle to the second cycle there is an increase of 12.1 figure (16.8%). The highest value precycle stage at 82 and 86 as well as the first cycle of the second cycle of 92. It is clear that from the stage of the first cycle precycle to an increase of 4 digits (5.4%), from the first cycle to the second cycle an increase of 6 figures ( 15.4%), and from the second cycle precycle to an increase of 10 points (21.6%). The lowest value obtained precycle stage at 66 and 70 as well as the first cycle of the second cycle of 76. thus, can be affirmed that the step of the first cycle precycle to an increase of 4 digits (6.1%), from the first cycle to the second cycle there is an increase of 6 figures (11.4%), and from the second cycle precycle to an increase of 10 points (15.2%). Percentage from precycle was obtained by 20% and the first cycle was obtained by 56% and the second cycle of 100%. It seems clear that the step of the first cycle precycle to an increase of 36%, from the first cycle to the second cycle there is an increase by 44%, and from the second cycle precycle to an increase of 80%. Thus, student achievement in the learning of Natural Sciences at the material Energy and its amendment of precycle until the second cycle occurs a significant increase.